Representative volume elements for the simulation of isotropic composites highly filled with monosized spheres. (February 2019) - de Francqueville, Foucault; Gilormini, Pierre; Diani, Julie
Abstract: A method is proposed for generating reliable representative volume elements (RVEs) that allows reducing the statistical analysis required for the simulation of the mechanical behavior of isotropic composites highly filled with monosized spheres. The method combines (i) an algorithm inspired from molecular dynamics and associated with an analytical equation of state, and (ii) a geometrical analysis using the two-point correlation function and a nearest-neighbor distribution function. A restrictive selection process is defined, which leads to microstructures reasonably close to randomness and isotropy. The pertinence of the proposed generation and selection of RVEs is confirmed by the simulation of their elastic behavior with the finite element method. In particular, it is shown how the selection procedure allows reducing the computational effort required to reach reliable elastic moduli by operating on a limited number of suitable RVEs. The results are in good agreement with the generalized self-consistent model and with original experimental data obtained on a composite where an acrylate matrix was reinforced by sifted glass beads.